2020
DOI: 10.14710/dmj.v9i3.27495
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plyometrics Training on Explosive Power of Medical Students in Diponegoro University

Abstract: Introduction : Explosive power are the combination maximum strength and maximum velocity. High value of muscle strength and velocity can lead to good measurement of explosive power. Plyometrics training known as an exercise that can increased explosive power. This exercise is really popular among athletes and has proven to increase their explosive power. However, there’s still no further study that measured explosive power on medical students after given plyometrics training treatment. Methods : Quasi experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Bone density changes with different sports. 1 Strength sports have the highest bone density, endurance sports have the lowest bone density, and male and female athletes show similar changes. Studies have found that weightlifters have the highest bone density among sports items by comparing muscle isometric contraction strength.…”
Section: Introductionmentioning
confidence: 93%
“…Bone density changes with different sports. 1 Strength sports have the highest bone density, endurance sports have the lowest bone density, and male and female athletes show similar changes. Studies have found that weightlifters have the highest bone density among sports items by comparing muscle isometric contraction strength.…”
Section: Introductionmentioning
confidence: 93%
“…Dasar pemikiran latihan plyometric adalah bahwa ketegangan otot maksimal akan meningkat ketika otot aktif diregangkan secara cepat (Pandoyo et al, 2020). Menurut (Sugiri, 2012) menjelaskan bahwa hingga saat ini plyometric untuk anggota gerak atas masih menerima lebih sedikit perhatian.…”
Section: Pendahuluanunclassified